A liquid waste service agreement between the Tamale Metropolitan Assembly, Ghana, and private sanitation service providers is ensuring safely managed sanitation services for over 950,000 households living in the Tamale Metropolitan Area - CGIAR Research Program on Water, Land and Ecosystems (2021)
Building on more than a decade of research and engagement, WLE/IWMI/RUL strengthened the capacity of the Tamale Metropolitan Assembly (TaMA) to implement market-based sanitation initiatives that deal with the disposal of fecal sludge (FS) from septic systems. It supported development of a liquid waste service agreement between TaMA and private sanitation service providers to ensure desludging at a designated treatment facility. As a result, more than 950,000 Tamale inhabitants now benefit from safely managed sanitation services.